Paclitaxel and the dietary flavonoid fisetin: a synergistic combination that induces mitotic catastrophe and autophagic cell death in A549 non-small cell lung cancer cells - Klimaszewska-Wisniewska, Anna (Cancer Cell Int, 2016)
BACKGROUND: The use of the dietary polyphenols as chemosensitizing agents to enhance the efficacy of conventional cytostatic drugs has recently gained the attention of scientists and clinicians as a plausible approach for overcoming the limitations of chemotherapy (e.g. drug resistance and cytotoxicity). The aim of this study was to investigate whether a naturally occurring diet-based flavonoid, fisetin, at physiologically attainable concentrations, could act synergistically with clinically achievable doses of paclitaxel to produce growth inhibitory and/or pro-death effects on A549 non-small cell lung cancer cells, and if it does, what mechanisms might be involved. METHODS: The drug–drug interactions were analyzed based on the combination index method of Chou and Talalay and the data from MTT assays. To provide some insights into the mechanism underlying the synergistic action of fisetin and paclitaxel, selected morphological, biochemical and molecular parameters were examined, including the morphology of cell nuclei and mitotic spindles, the pattern of LC3-II immunostaining, the formation of autophagic vacuoles at the electron and fluorescence microscopic level, the disruption of cell membrane asymmetry/integrity, cell cycle progression and the expression level of LC3-II, Bax, Bcl-2 and caspase-3 mRNA. RESULTS: Here, we reported the first experimental evidence for the existence of synergism between fisetin and paclitaxel in the in vitro model of non-small cell lung cancer. This synergism was, at least partially, ascribed to the induction of mitotic catastrophe. The switch from the cytoprotective autophagy to the autophagic cell death was also implicated in the mechanism of the synergistic action of fisetin and paclitaxel in the A549 cells. In addition, we revealed that the synergism between fisetin and paclitaxel was cell line-specific as well as that fisetin synergizes with arsenic trioxide, but not with mitoxantrone and methotrexate in the A549 cells. CONCLUSIONS: Our results provide rationale for further testing of fisetin in the combination with paclitaxel or arsenic trioxide to obtain detailed insights into the mechanism of their synergistic action as well as to evaluate their toxicity towards normal cells in an animal model in vivo. We conclude that this study is potentially interesting for the development of novel chemotherapeutic approach to non-small cell lung cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12935-016-0288-3) contains supplementary material, which is available to authorized users.